Quantitative ATR-IR analysis of anisotropic polymer films: Surface structure of commercial PET - Kirov, K; Assender, H (2005)
A commercial PET film has been characterized using variable-angle ATR-IR spectroscopy to create a depth profile of the surface. The anisotropic optical constants (n, k) of the film were extracted from the reflectivity spectra assuming that the depth region probed at each angle of incidence is homogeneous. The refractive index n, absorption index k, and absorption coefficient K spectra of the film were then employed to calculate the trans / gauche content of PET and the extent of trans conformer orientation as a function of depth of penetration. The trans-PET content of the commercial film we analyzed changes from 78% at a depth of penetration of 0.4 μm to 61% at a depth of penetration of 1.1 μm. Results of the orientational analysis of the film are presented, and problems specific to ATR-IR spectroscopy in such analysis are also discussed. © 2005 American Chemical Society.